A multi-layer framework for quality of context in ubiquitous context-aware systems. Issue 2 (4th June 2018) - Al-Shargabi, Asma Abdul Ghani; Siewe, Francois
Abstract : Purpose: This paper aims to introduce a comprehensive framework for quality of context in pervasive context-aware systems. The framework includes the context quality characteristics, the quality policy, the quality calculation methods and the quality control algorithm. Design/methodology/approach: This study used the constructive research method to introduce the framework. The data of a context-aware flooding prediction system to evaluate the approach were used. Findings: The framework improves the quality of captured context by resolving the missing, error context and the context conflicts using the quality characteristics and quality control process that are introduced in the framework. Originality/value: This work is original. It is based on the author's PhD work in De Montfort University.